The Influence of Picture Number Card Media on the Introduction to Number Concepts and Critical Thinking Abilities in Early Childhood - Nikmah, Muzan Dahluil; Jannah, Miftakhul; Fitri, Ruqoyyah (Studies in Philosophy of Science and Education, 2025)
This research aims to determine the effect of picture number card media on the introduction of number concepts and critical thinking abilities of children aged 4–5 years. Initial observations at PGTK As-Sakinah showed that these abilities had not yet developed optimally. The study involved 30 children, consisting of 46.67% boys and 53.33% girls, divided equally into an experimental group (TKA 1) and a control group (TKA 2). A quantitative experimental method was used, with data analysis through JASP 0.19.10, employing descriptive analysis and the Mann-Whitney U test. The descriptive results indicated a clear difference, with the experimental group achieving a gain score of 6.13 compared to 2.4 in the control group for the introduction of number concepts. In terms of critical thinking, the experimental group had a gain score of 2.4, while the control group scored 0.87. Hypothesis testing showed a p-value of <0.001, indicating that p was smaller than 0.05. Thus, it can be concluded that the use of picture number card media significantly influences the development of number concept understanding and critical thinking abilities in children aged 4–5 years.